Psychological Barriers of Teacher and Students Interaction and Ways of their Effective Overcoming - Hirnyak, Andriy; Vasylkiv, Olena (Psychological Prospects Journal, 2019)
The typical psychological barriers that arise between teacher and students as the main subjects of educational interaction are singled out on the basis of communicative, hermeneutic and systemic-activity approaches in psychology. The authors reveal the essential content of indicated barriers and criteriologicallycombine them into four groups: 1) barriers predetermined by personality and professional characteristics of a teacher, 2) barriers preconditioned by psychological and physical peculiarities of a student, 3) barriers predetermined by specificity of a subject interaction  (educational content), 4) barriers caused by adverse factors of material or social environment where educational interaction takes place. On the basis of reflexive analysis of the manifestation forms of specified groups of psychological barriers, a peculiar psychological portrait of a person is created that potentially builds similar obstacles in interpersonal interaction. Also, the article outlines the main ways (methods) of effective overcoming of psychological barriers in permanent process of dialogical communication of educational activity subjects.These specified ways include: acquiring of pedagogical work experience, development of constituents (primarily social perception and reflection) within the framework of active social and psychological training and improvement of a general culture of a teacher (professional, inner personality and social competence, increase of indicators of general level of personality and intellectual development). At the same time, the thesis is suggested that minimization and overcoming of possible interference barriers is most effective under conditions of using four strategies dialogue conduction, which, best of all, can be used alternately, guided by the logical and canonical structure of the act: agreement (namely achievement of the consonance of values, meanings, senses), persuasion (logical proof, propaganda, verbal recommendation, suggestion), cooperation (approval of views and actions, empathy, mutual assistance, etc.), authority (expert examinations, attractive influences, reliance on traditions , preconceptions and social norms).